Presynaptic calcium channels in rat cortical synaptosomes: fast- kinetics of phasic calcium influx, channel inactivation, and relationship to nitrendipine receptors - Suszkiw, JB (J Neurosci, 1986)
Fast-mixing and rapid-filtration techniques were used to analyze the kinetics of potassium-depolarization-dependent (delta K+ = 47.5 mM) influx of 45Ca into synaptosomes, in the time range from 50 msec to 5 sec. The results are consistent with the presence in synaptosomes of a homogeneous population of voltage-sensitive Ca channels. With 1 mM Cao in the medium, the delta K+-dependent Ca influx has a single- exponential time course with the half-life, t1/2 approximately 0.5–0.7 sec. Ca influx, measured between 0.1 and 10 mM Cao, shows half- saturation (KCa) at 1.5 mM Cao and has the limiting value (JCamax) of 5.9 nmol/sec/mg protein, or a current of approximately 0.06 pA/micron2 surface area. The estimated density of functional Ca channels is 0.6–6 micron-2. Voltage- and time-dependent inactivation of Ca channels was measured in synaptosomes predepolarized in 52.5 mM Ko+ with Ca omitted from the medium. Channel inactivation is a single-exponential process with a half-life of t1/2 approximately 2.3 sec. Channel recovery in 5 mM Ko+ media is likewise a single-exponential process with a half-life of t1/2 approximately 4.3 sec. The slower rate of voltage-dependent channel inactivation than of decay of Ca influx suggests that Ca entry into synaptosomes terminates by a mechanism that depends on Ca influx itself. Synaptosomes contain 200 fmol/mg protein, or approximately 6 micron-2 high-affinity (KD = 0.12 nM) 3H-nitrendipine binding sites; however, nitrendipine at concentrations greater than 10(4) X KD is without effect on the phasic influx of Ca measured at 215 msec with either 1.0 or 0.1 mM Cao. This suggests that Ca channels characterized in this study belong to a class of dihydropyridine-insensitive channels.